MANAGEMENT OF CEREBRAL PALSY WITH SAMVARDHANA GHRITA AND CERTAIN AYURVEDIC PROCEDURES - A CLINICAL STUDY - Rathia Satyawati,; Kori V K,; S Rajagopala,; Patel K S, (International Journal of Applied Ayurved Research, 2016)
Background: WHO estimates that about 10% of the world population and 3.8% of the In-dian population have some form of disability. Among them the prevalence of Cerebral Palsy is 3 per 1000 live births. Aim: To assess the efficacy of Samvardhana Ghrita with Udvartana and Abhyanga in Cerebral Palsy. Materials and Methods: In this study, 8 patients com-pleted the treatment. Samvardhana Ghrita was given orally for 62 days with Udvartana (5days), Abhyanga (5days), followed by Nadi Swedana. Method of the study is simple ran-dom sampling. Result: Improvement in growth (Weight, Height and Chest Circumference), developmental milestone (Neck Holding) and motor component (muscle bulk and Power) were observed. This study shows that improvement was observed in 25% patients. Conclu-sion: Though disease is not curable, but through Ayurvedic management protocol can show a better direction by improving the quality of life of those children.